PEMANFAATAN DATA E-KTP DALAM PROSES VALIDASI PESERTA MUSABAQOH TILAWATIL QUR’AN (MTQ) - Abdulloh, Abd Hamid (Jurnal Review Politik, 2014)
MusabaqohTilawatil Quran (MTQ) in Indonesia can be considered as a religious activity carried out regularly, with large amount of government’s funding. MTQ cannot be separated from the social dimension. Therefore, competition among regions to be the main champion is an inevitable matter. This has implications on the authenticity of the participants in terms of data validationprocess. This article has been written based on field and literature researches.It focuses on the problem of minimizing and eradicating the deficiencies and irregularities,which might occurduring the MTQ activities, related to a number of crucial issues such as age of the participants, sex, fingerprints, and address of the participants. The resultof the study indicates that in order to validate the data, the participants should use the e-ID card technology. Through the card reader and access to the Dispenduk’s data warehousethe authenticity of the data can be authenticated.